Enhanced Structural And Electrical Properties Of Lead-Free Y-Doped (K, NA) NBO3 Thin Films - Mat Harttar @ Mohd Hatta, Maziati Akmal; Azlan, Umar Al-Amani; Abd Rashid , Mohd Warikh; Azmi, Nurul Azuwa (Penerbit UTM Press, 2015)
-